Pemilihan Teknik Sampling yang Tepat Dalam Penelitian Kualitatif: Literature Review - Andriani, Desi; Maritasari, Donna Boedi; Laela, Ismiatul; Husnadia, Siti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Qualitative research aims to understand the deep meaning of a social phenomenon, making the selection of the right sampling technique crucial in obtaining relevant and rich information. This systematic literature study aims to outline various qualitative sampling techniques suitable for different types of qualitative research, such as phenomenology, ethnography, case studies, or grounded theory. The author collects and analyzes information from various literature sources, applying content analysis and thematic synthesis to identify and synthesize the appropriateness of sampling techniques with the characteristics of qualitative research. The results of this research provide a deep understanding of the relationship between sampling techniques and the specific objectives of the research and the actual field conditions. The implications of this research are to provide practical guidance for qualitative researchers in designing robust and valid methodologies, ensuring that the data collected is truly representative to achieve the desired depth of understanding. Thus, the quality and credibility of qualitative research can be significantly enhanced, helping researchers make more precise methodological decisions and obtain more comprehensive findings.